Development and validation of the patient-reported "Facial Function Scale" for facioscapulohumeral muscular dystrophy. Issue 9 (24th April 2023) - Mul, Karlien; Wijayanto, Feri; Loonen, Tom G. J.; Groot, Perry; Vincenten, Sanne C. C.; Knuijt, Simone; Groothuis, Jan T.; Maal, Thomas J. J.; Heskes, Tom; Voermans, Nicol C.; Engelen, Baziel G. M. van
Abstract: Purpose: Facial weakness and its functional consequences are an often underappreciated clinical feature of facioscapulohumeral muscular dystrophy (FSHD) by healthcare professionals and researchers. This is at least in part due to the fact that there are few adequate clinical outcome measures available. Methods: We developed the Facial Function Scale, a Rasch-built questionnaire on the functional disabilities relating to facial weakness in FSHD. A preliminary 33-item questionnaire was created based on semi-structured interviews with 16 FSHD patients and completed by 119 patients. For reliability studies, 73 patients completed it again after a two-week interval. Data were subjected to semi-automated Rasch analysis to select the most appropriate item set to fit model expectations. Results: This resulted in a 25-item unidimensional, linear-weighted questionnaire with high internal consistency (person separation index = 0.92) and test–retest reliability (patients' locations ICC = 0.98 and items' locations ICC = 0.99). Good external construct validity scores were obtained through correlation with the Communicative Participation Item Bank questionnaire, examiner-reported Facial Weakness Score and facial weakness subscale of the FSHD evaluation score (respectively r  = 0.733, r  = −0.566, and r  = 0.441, all p  < 0.001). Conclusions: This study provides a linear-weighted, clinimetrically sound, patient-reported outcome measure on the functional disabilities relating to facial weakness in FSHD, to enable further research on this relevant topic. Implications for rehabilitation: Facial weakness and its functional consequences are an often underappreciated clinical feature of facioscapulohumeral muscular dystrophy (FSHD), both in symptomatic treatment and in research. To enable the development and testing of therapeutic symptomatic interventions for facial weakness, clinical outcome measures are required. This study provides a linear-weighted, clinimetrically sound, patient-reported outcome measure on the functional disabilities relating to facial weakness in FSHD patients.